2011
DOI: 10.1021/cb200298g
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Virulence in Pathogenic Bacteria Using Synthetic Quorum-Sensing Modulators under Native Conditions on Plant Hosts

Abstract: Quorum sensing (QS) is often critical in both pathogenic and mutualistic relationships between bacteria and their eukaryotic hosts. Gram-negative bacteria typically use N-acylated L-homoserine lactone (AHL) signals for QS. We have identified a number of synthetic AHL analogues that are able to strongly modulate QS in culture-based, reporter gene assays. While informative, these assays represent idealized systems and their relevance to QS under native conditions is often unclear. As one of our goals is to utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 56 publications
1
68
0
Order By: Relevance
“…5) (198). Other studies from the Blackwell lab have demonstrated the applicability of various compounds against the pathogenic actions of E. carotovora on Solanum tuberosum (potato) and of P. syringae on Phaseolus vulgaris (green bean), and several compounds showed promising results modulating quorum sensing in both bacteria, though the timing and dosage of treatments, especially in the potato model, were critical (199,201). In another example of cross-inhibition, a high-throughput chemical screen of approximately 35,000 compounds led to the identification of 15 small molecules that inhibited the LuxN/AI-1 QS circuit in V. harveyi (129).…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…5) (198). Other studies from the Blackwell lab have demonstrated the applicability of various compounds against the pathogenic actions of E. carotovora on Solanum tuberosum (potato) and of P. syringae on Phaseolus vulgaris (green bean), and several compounds showed promising results modulating quorum sensing in both bacteria, though the timing and dosage of treatments, especially in the potato model, were critical (199,201). In another example of cross-inhibition, a high-throughput chemical screen of approximately 35,000 compounds led to the identification of 15 small molecules that inhibited the LuxN/AI-1 QS circuit in V. harveyi (129).…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…The utility of synthetic AHL analogues (SAHLAs) as modulators of QS under native conditions (i.e., whilst the bacteria colonizes its natural host) has also been validated in several systems, including: (i) inhibiting virulence factor production by P. carotovorum in infections of Solanum tuberosum (potato) 33 , (ii) enhancing QS-mediated nodulation between strains of Sinorhizobium meliloti and its legume host Medicago truncatula 34 , and (iii) altering V. fischeri bioluminescence in the light organ of Euprymna scolopes , the bobtail squid 36 . The success of these trials is establishing both the concentration and dosing times required for effectively regulating QS signaling in situ .…”
Section: Introductionmentioning
confidence: 99%
“…While B. thuringiensis expresses a unique lactonase, AiiA (13), R. erythropolis expresses three QQ activities, a lactonase (QsdA), an acylase, and a reductase (28,33,34). Aside from the use of biocontrol agents (13,32), QQ molecules (24,27), and QQ transgenic plants (12,16), a biostimulation approach was recently proposed (6,7). It consists of the application of a biodegradable agent, gamma-caprolactone (GCL), to stimulate in the rhizosphere of Solanum tuberosum the growth of endogenous AHL-degrading bacteria (hence the name "biostimulation" to describe this technique).…”
mentioning
confidence: 99%